Backward Chaining Method for Diagnosis Disorders of Women's Menstrual Cycle - Sri Rahmadani; Mhd. Furqan; Sriani (Jurnal Mantik, 2022)
Menstrual cycle disorders are disorders of the female reproductive system that occur when women do not care for and maintain their health. From disruption of the menstrual cycle can be a disease that is dangerous for women. The problem that occurs is that many women rarely want to check the symptoms of menstrual cycle disorders. This is due to the laziness of going to the doctor or the distance from where the doctor is and the reason for the high cost of making a diagnosis to a doctor. So we need an expert system application to diagnose the disease from menstrual symptoms. In this study, the method used is Backward Chaining, the Backward Chaining method solves every symptom that appears and continues on to the next symptom in the same rule so that a decision tree is formed. Utilization of an expert system in the application can help women to find out the diagnosis of the menstrual cycle in the form of: hypermenorrhea (menorrhagia), hypomenorrhea, polimenorrhea, oligomenorrhea, and amenorrhea. The application is able to display diseases from menstrual symptoms quickly and accurately.